2008
DOI: 10.1103/physrevlett.100.137401
|View full text |Cite|
|
Sign up to set email alerts
|

Evidence of Orbital Reconstruction at Interfaces in UltrathinLa0.67Sr0.33MnO3Films

Abstract: Linear dichroism (LD) in x -ray absorption, diffraction, transport and magnetization measurements on thin La 0.7 Sr 0.3 MnO 3 films grown on different substrates, allow identification of a peculiar interface effect, related just to the presence of the interface. We report the LD signature of preferential 3d-e g (3z 2 -r 2 ) occupation at the interface, suppressing the double exchange mechanism.This surface orbital reconstruction is opposite to that favored by residual strain and is independent of dipolar field… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
158
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 276 publications
(180 citation statements)
references
References 27 publications
14
158
1
Order By: Relevance
“…We use Slater integrals reduced to 70% and a tetragonally distorted octahedral crystal field (D4h symmetry), with Ds = ±0.186 eV, Dt = ±0.025 eV, 10Dq = 1.1 eV for the cubic crystal field splitting and three valence states (Mn 3+ , 0.7Mn 3+ + 0.3Mn 4+ , Mn 4+ ). 10 The preferential occupation of the d3z 2 (dx 2 -y 2 ) orbital is induced by the positive (negative) signs of Ds and Dt, which is corresponding to an in-plane compressive (tensile) strain. Among the simulated spectra the two with compressive strain and Mn 3+ and 0.7Mn 3+ + 0.3Mn 4+ valence states are more similar to the experimental spectra of the 3, 6 and 8-u.c.…”
Section: -7mentioning
confidence: 99%
See 1 more Smart Citation
“…We use Slater integrals reduced to 70% and a tetragonally distorted octahedral crystal field (D4h symmetry), with Ds = ±0.186 eV, Dt = ±0.025 eV, 10Dq = 1.1 eV for the cubic crystal field splitting and three valence states (Mn 3+ , 0.7Mn 3+ + 0.3Mn 4+ , Mn 4+ ). 10 The preferential occupation of the d3z 2 (dx 2 -y 2 ) orbital is induced by the positive (negative) signs of Ds and Dt, which is corresponding to an in-plane compressive (tensile) strain. Among the simulated spectra the two with compressive strain and Mn 3+ and 0.7Mn 3+ + 0.3Mn 4+ valence states are more similar to the experimental spectra of the 3, 6 and 8-u.c.…”
Section: -7mentioning
confidence: 99%
“…One of the most interesting examples is phase transition from metal in bulk form to insulator in thin film, as exhibited by several metallic oxides, such as SrVO 3 , 1 LaNiO 3 , 2,3 SrRuO 3 , 4 and La 1x Sr x MnO 3 . [5][6][7][8][9][10][11] Researchers have worked to minimize several extrinsic effects of interfacial chemical or oxygen disorders by optimizing growth conditions, but the dead layer in which electrical conductivity or ferromagnetism disappear still remains.…”
Section: Introductionmentioning
confidence: 99%
“…The spectral difference (I(E||a)-I(E||c), linear dichroism) implies a preferential occupancy of the 3d x 2 Ày 2 orbital at both 80 and 300 K. The result is in good agreement with the theoretically calculated result for LSMO film under tensile strain. 18,24 X-ray magnetic circular dichroism measurements…”
Section: X-ray Linear Dichroism Measurementsmentioning
confidence: 99%
“…In the La 1-x Sr x MnO 3 solid solution, the electron occupancy of the e g doublet depends on the strength of the JahnTeller distortion, which in turn is determined by the hole doping level, x (Tokura and Nagaosa, 2000). In epitaxial thin films, however, similarly to the Jahn-Teller distortion, misfit strains have the ability to break the x 2 − y 2 /3z 2 − r 2 orbital degeneracy (Fang et al, 2000) as recently confirmed by X-ray linear dichroism investigations (Huijben et al, 2008;Tebano et al, 2008;Pesquera et al, 2012). A thorough investigation taking into account the attenuation of the signal with the depth in the sample, suggests that the observed X-ray linear dichroism is rather a consequence of the superposition of interfacial and free surface effects (Pesquera et al, 2012).…”
Section: Misfit Strainmentioning
confidence: 82%